PODCAST ROOM RESERVATION APPLICATION USING EXTREME PROGRAMMING METHOD - Matthew, Randy; Lee, Francka Sakti (Jurnal Techno Nusa Mandiri, 2024)
In the era of globalization, information technology has become crucial in enhancing the productivity of information processing across various industries. Data management ensures smooth operations and informed decision-making. Podcasts have emerged as significant mediums for information consumption and entertainment, with an increasing number of listeners seeking high-quality content. Producing quality podcasts requires adequate facilities such as advanced recording equipment and acoustically suitable studio spaces. Development methodologies like Extreme Programming emphasize improving functionality and technical implementation. Reservations for podcast studios play a crucial role in scheduling recordings, with online booking systems enabling easy and efficient reservations, albeit requiring intensive individualized services. The capability of reservation systems to provide quick, accurate, and precise information can influence customer experiences and purchasing decisions. The integration of information technology and online reservations is key to optimizing podcast production and distribution, enhancing operational efficiency for service providers, while providing a satisfying experience for listeners. Although the system has yet to be fully implemented, it is designed to streamline booking processes and reduce manual intervention, which is anticipated to lead to significant improvements in both operational efficiency and customer satisfaction.